EFFECT KNOWLEDGE MANAGEMENT AND PERFORMANCE AT THE KENYA REVENUE AUTHORITY - Muturi, Elizabeth (American Journal of Data, Information and Knowledge Management, 2021)
Purpose: The real challenge is the use of technology to continuously promote KM uptake in organizations with a different culture, more so government institutions, ensuring at the same time that knowledge creation, sharing and usage becomes more efficient and transparent.. The general objective of the study was to evaluate effect knowledge management and performance at the Kenya revenue authority. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study concludes that, majority of the respondents agree that knowledge sharing through the KM portal reduces the knowledge accessibility process which saves on man-hour. It 66 also concludes that using the KM portal reduces the knowledge transfer rate within KRA. Also on-line KM sharing process improves efficiency in transferring critical knowledge within KRA and has improved knowledge creating and sharing levels. It is less expensive to do on-line knowledge sharing than the traditional methods. Finally, knowledge management has helped KRA in improving performance while also helping KRA to control of the knowledge management process. The study further concludes that indeed knowledge management leveraged on technology has a positive relationship with organizational performance. This implies that with the adoption of knowledge management based on technology, performance is likely to be enhanced. Recommendations: There is a need for KRA Kenya Revenue Authority to sensitize the employees on the KM systems it has in place and how they will be of advantage to them in terms of increasing their output levels. Given the positive response from the employees that they are willing to embrace knowledge creation, sharing and usage in the long term, there is need for Kenya Revenue Authority to keep on developing new systems and improving on the existing ones on a need to need basis. The new systems and improved existing ones will ensure that KM leveraged on technology is sustainable and thus the performance levels will improve